Q. 64.0( 28 Votes )

Simplify.

i. 5√3 + 8√3

ii. 9√5 – 4√5 + √125

iii. 7√48 – √27 – √3

iv.

Answer :

i. 5√3 + 8√3


5√3 + 8√3 = (5 + 8)√3


5√3 + 8√3 = 13√3


ii. 9√5 – 4√5 + √125


9√5 – 4√5 + √125 = 9√5 – 4√5 + √(5 × 5 × 5)


9√5 – 4√5 + √125 = 9√5 – 4√5 + √(5 × 5 × 5)


9√5 – 4√5 + √125 = 9√5 – 4√5 + 5√5


9√5 – 4√5 + √125 = (9 – 4 + 5)√5


9√5 – 4√5 + √125 = 10√5


iii. 7√48 – √27 – √3


7√48 – √27 – √3 = 7√(2 × 2 × 2 × 2 × 3) – √(3 × 3 × 3) – √3


7√48 – √27 – √3 = 7×4√3 – 3√3 – √3


7√48 – √27 – √3 = 28√3 – 3√3 – √3


7√48 – √27 – √3 = (28 – 3 – 1)√3


7√48 – √27 – √3 = 24√3


iv.





Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.